2018
DOI: 10.1080/14459795.2018.1467946
|View full text |Cite
|
Sign up to set email alerts
|

The neuroscience and neuropsychology of gambling and gambling addiction: an introduction to the special issue

Abstract: Neuroscience research on gambling, including neuropsychological, neuroimaging, and psychophysiological experiments, is often regarded as aligned with the 'brain disease model of addictions' . We assert that a bio-psycho-social framework represents the consensus view of disordered gambling, giving equal weighting to biological and psychosocial predisposing factors (and their interactions). Within this framework, we highlight three ways in which neuroscience can inform gambling research -none of which rely on on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Along with difficulties in emotion regulation, Hormes and colleagues (2014) have shown that problematic Facebook users tend to also report high levels of craving. Craving is a powerful and automatic experience that motivates people to seek out the craved activity (Marlatt, 1987;Spada, Caselli, Slaifer, Nikcevic, & Sassaroli, 2014) and is characterized by strong physiological 'markers' typically involved in substance and behavioural addictions (e.g., Blaine, Nautiyal, Hart, Guarnaccia, & Sinha, 2018;Wise & Koob, 2014;Clark & Goudriaan, 2018). It follows that a strong urge to access social networking sites might be a predictor of PFU.…”
Section: Introductionmentioning
confidence: 99%
“…Along with difficulties in emotion regulation, Hormes and colleagues (2014) have shown that problematic Facebook users tend to also report high levels of craving. Craving is a powerful and automatic experience that motivates people to seek out the craved activity (Marlatt, 1987;Spada, Caselli, Slaifer, Nikcevic, & Sassaroli, 2014) and is characterized by strong physiological 'markers' typically involved in substance and behavioural addictions (e.g., Blaine, Nautiyal, Hart, Guarnaccia, & Sinha, 2018;Wise & Koob, 2014;Clark & Goudriaan, 2018). It follows that a strong urge to access social networking sites might be a predictor of PFU.…”
Section: Introductionmentioning
confidence: 99%
“…These could be used to design and improve more effective psychological treatments in the future, along with empirical-based prevention campaigns. Furthermore, these studies allow us to have more reliable and objective measures of craving, specify the underlying brain mechanisms of psychological therapies or help to improve responsible gambling advertising policies (Clark & Goudriaan, 2018 ). In this sense, early detection and prevention could be better assessed and designed on the basis of brain reactivity measures.…”
mentioning
confidence: 99%
“…Gambling Disorder (GD) appears to result from a combination of factors interacting at different levels [1] and can be considered a bio-psycho-social disorder [2,3]. Firstly, according to the literature review, individuals with previous psychopathological disorders, such as substance abuse, mood, anxiety, and personality disorders, are more likely to suffer from GD [1,4,5].…”
Section: Introductionmentioning
confidence: 99%